THE ROLE OF TRAINING AND COMPETENCE IN IMPROVING EMPLOYEE PERFORMANCE AT BANK BNI TULUNGAGUNG: WORK MOTIVATION AS A MEDIATION VARIABLE - Firdaus Ali Syabana; Siti Asiyah; Eka Farida (International Journal of Cultural and Social Science, 2025)
The banking industry faces growing competition due to technological advances, shifting consumer behavior, and digital innovation. In this context, the success of Bank Negara Indonesia (BNI) Tulungagung Branch depends on the quality of its human resources (HR), which serve both operational and strategic roles. This study aims to examine the effect of training and competence on employee performance, with work motivation as a mediating variable. A quantitative explanatory research design was applied, involving 70 employees as respondents. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) via SmartPLS 3.0. The analysis confirmed strong validity and reliability (loading factor 0.731–0.912; Cronbach’s Alpha > 0.70). Training and competence explained 70.6% of performance variance and 71.5% of motivation variance. Training significantly influenced motivation, while competence had a significant effect on performance. However, motivation did not significantly affect performance and did not mediate the relationship. Thus, performance enhancement is best achieved through direct training and competency development.